Comparison study between single enzyme and multienzyme complex in distiller’s dred grains with soluble supplemented diet in broiler chicken - Min-Jin Kwak; Dong-Jin Ha; Min Young Park; Ju Young Eor; Kwang-Youn Whang; Younghoon Kim (Journal of Animal Science and Technology, 2024)
Upregulation of the nutritional value of feed is the major target of various studies in the livestock industry, and dietary enzyme supplementation could aid in digesting the nondegrading nutrients of grains in feed ingredients. Dried distillers’ grains with solubles (DDGS) is a byproduct of the fermentation process in the beverage industry and can be used as a large supply source of fiber in feed. Therefore, we conducted an experiment with male broiler chickens to investigate the effect of various types of enzymes on DDGS and compare the efficacy of single enzyme and multienzyme complexes on growth performance and gut environments in broiler chickens. We used 420 1-day-old broiler chickens (Ross 308), and they were allotted into 4 dietary treatments with seven replications (CON, corn-soybean meal [SBM] diet; NC, DDGS supplemented diet; SE, 0.05 % of mannanase supplemented DDGS-based diet; MC, 0.10% of multienzyme complex (mannanase and xylanase, glucanase) supplemented DDGS-based diet. The dietary exogenous enzyme in the DDGS-supplemented diet could improve growth performance as much as the growth of the control group, and digestibility of dry matter, crude protein, and gross energy were significantly increased by enzyme addition in groups of chicks fed DDGS-supplementation diet. Moreover, the populations of pathogenic bacteria, coliforms, and Bacteroidetes were significantly decreased by enzyme supplementation, which might lead to improved gut mucus-secreting cells and inflammatory cytokines in the jejunum. Collectively, dietary single enzyme and multienzyme complexes could improve gut environments, including intestinal immune responses and gut microbial population, and lead to improvement of growth performance in broiler chickens.